False Target Deceptive Jamming for Countering Missile-Borne SAR - Xiaodong He; Jun Zhu; Jun Wang; Dongping Du; Bin Tang (2014 IEEE 17th International Conference on Computational Science and Engineering, 2014)
A false target deceptive jamming method for countering missile-borne SAR is proposed in this paper, which is on the basis of false target phase template modulation to intercepted missile-borne SAR signal to generate jamming signal. The jammer receiver calculates the phase of missile-borne SAR signal, and modulates the phase of Doppler frequency and backscattering coefficient data based on range bins, which is calculated on the basis of the expected position in range direction in advance, to the phase of the missile-borne SAR transmitted signal. Then, the jamming system calculates and modulates the phase of Doppler frequency in azimuth direction to every range bin phase of jamming signal and delays corresponding time. Finally, the jammer sums every range bins jamming signal and retransmits it to the missile-borne SAR direction.